Results of proteinuria measurement using semiquantitative dipstick in children with fever or nephrotic syndrome - Chatidjah Alaydrus; Yati Soenarto; M. P. Damanik (Indonesian Pediatric Society, 2008)
Background Proteinuria is a major determinant of the progressionof renal disease. Quantitative measurement of proteinuria withina 24-hour period of urine collection was the accepted method ofevaluation, but is tedious and prone to error in the absence of areliable collection. We evaluated the diagnostic value of AUTIONSticks 10 TA to diagnose proteinuria in children with fever andnephrotic syndrome.Methods This study was conducted at the pediatric ward of SardjitoHospital. Proteinuria levels were measured using semiquantitativedipstick methods with AUTION Sticks 10 TA using a 24-hoururine sample collected at the first examination until the followingday. Proteinuria level was also measured by Esbach method as goldstandard.Results A total of 120 children aged 16 years old were recruited. Inthe fever group, AUTION Sticks 10 TA couldn’t be used for thediagnostic test. AUTION Sticks 10 TA +2 to diagnose intermediateproteinuria produced a sensitivity of 60%, a specificity of 89%, apositive predictive value of 43% , a negative predictive value of94%, a positive likelihood ratio of 5.4, a negative likelihood ratio of0.45. To diagnose nephrotic proteinuria, AUTION Sticks 10 TA+3/+4 produced a sensitivity of 90%, a specificity of 91%, a positivepredictive value of 96%, a negative predictive value of 77%, apositive likelihood ratio of 10, a negative likelihood ratio of 0.11.Conclusion AUTION Sticks 10 TA +2 is sufficiently accuratefor a diagnostic test of intermediate proteinuria (Esbach value)while +3/+4 is sufficiently accurate for a diagnostic test ofnephrotic proteinuria (Esbach value) in children. In the fevergroup, dipstick result can not explain the Esbach value.